Electronic voting : third International Joint Conference, E-Vote-ID 2018, Bregenz, Austria, October 2-5, 2018, Proceedings /: third International Joint Conference, E-Vote-ID 2018, Bregenz, Austria, October 2-5, 2018, Proceedings. (2018) - Unknown
No abstract available